Transparent super-smooth anti-icing surface and preparation method thereof
By forming regular nanostructures on the substrate surface and silane coupling modification and grafting flexible polymer molecular chains, the existing anti-icing surfaces are solved, and high transparency and excellent dynamic hydrophobic properties are achieved, which significantly delays the icing time.
Patent Information
- Application Number
- CN202510077546.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
AI Technical Summary
The existing anti-icing surface is difficult to take into account between transparency and anti-icing effects, and the lack of dynamic hydrophobicity is still inevitable.
The surface with transparent ultraslip anti-freeze properties was prepared by nanoimprinting and plasma etching.
High transparency and excellent dynamic hydrophobic performance are achieved, which significantly delays the icing time, significantly reduces the contact time of water droplets on the surface, and slows down the growth rate of ice crystals.
Smart Images

Figure CN119793852A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface functionalized coating preparation, and in particular relates to a transparent super-smooth anti-icing surface and a preparation method thereof. Background Art
[0002] In the past, anti-icing was mainly achieved through active methods such as heating and mechanical tapping. In recent years, with the development of materials science, passive anti-icing surfaces have received widespread attention, and transparent super-hydrophobic anti-icing surfaces have become a research hotspot in the fields of transportation, energy, and construction. There are two main aspects to consider in the preparation of anti-icing surfaces. One is to reduce the solid-liquid contact area, and the other is to reduce the solid-liquid contact time. In previous studies on anti-icing surfaces, static hydrophobicity, that is, the contact angle of water droplets on the surface, is often focused on. Super-hydrophobic surfaces effectively reduce the solid-liquid contact area and reduce the contact time to a certain extent by making the droplets form a contact angle greater than 150° and a rolling angle less than 10° with the surface. To achieve super-hydrophobicity, it is necessary to have a suitable surface roughness, such as micron and nano-scale rough structures, but in the actual preparation process, it is often difficult to balance the surface roughness and transparency. The reason is that although the construction of a rough structure is conducive to super-hydrophobicity, it will interfere with light transmission, resulting in reduced transparency. In addition, although static hydrophobicity can effectively delay its freezing time, it still inevitably causes icing.
[0003] Therefore, in comparison, high dynamic hydrophobicity, that is, reducing the contact time between the droplet and the surface, so that the droplet can quickly fall off the surface at a very small tilt angle, can more effectively prevent the occurrence of icing. Liquid-infused surface and liquid-like surface are representative surfaces with excellent dynamic hydrophobicity. However, although the liquid-infused surface can effectively improve the surface's anti-icing ability, due to the instability of the liquid on the liquid-infused surface, its effective working time is short and cannot be used in practice. The liquid-like super-slippery surface is composed of polymer chains with high fluidity. Since these polymer chains can easily achieve their configuration conversion when in contact with droplets, the adsorption and friction of droplets on the surface are greatly reduced, showing liquid-like characteristics, so it is called a liquid-like surface. The liquid-like super-slippery surface has extremely low contact angle hysteresis and excellent dynamic hydrophobic properties, so it can effectively achieve the anti-icing effect. At the same time, because its surface is not composed of actual liquid, it also has higher durability than the liquid-infused surface.
[0004] At present, there are two main types of liquid-like super-slippery surfaces used in the field of anti-icing: planar and non-planar. Planar liquid-like super-slippery surfaces are obtained by grafting high-fluidity polymer chains onto smooth surfaces, such as polydimethylsiloxane (PDMS) and perfluoropolyether (PFPE). However, planar liquid-like super-slippery coatings still have certain disadvantages in anti-icing performance. Due to their relatively large solid-liquid contact area, on the one hand, their heat transfer is faster, making surface droplets easier to freeze, and on the other hand, the binding force between ice and the surface is increased, making it difficult to remove accumulated ice. Non-planar liquid-like super-slippery coatings often have special microstructures, such as protrusions, depressions or other irregular shapes. These structures can effectively reduce the contact area, reduce friction and heat transfer rate, but similar to super-hydrophobic surfaces, these microstructures also reduce their transparency.
[0005] Therefore, it is of great significance to prepare a super-slippery surface that has both transparency and anti-icing effects. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a transparent super-slip anti-icing surface and a preparation method thereof.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a transparent super-slip anti-icing surface, comprising the following steps:
[0009] Coating a photoresist on the surface of the substrate, and then performing nanoimprinting to obtain a substrate with a regular nanostructure;
[0010] Plasma etching is performed on the substrate having the regular nanostructure to obtain an activated substrate having a nanocomposite structure;
[0011] The activated substrate surface with the nanocomposite structure is subjected to silane coupling modification and grafted with flexible polymer molecular chains to obtain the transparent super-slip anti-icing surface.
[0012] The present invention provides a method for preparing a transparent super-smooth anti-icing surface. First, a photoresist is coated on the surface of a substrate, and a surface with a regular nanostructure is obtained by nanoimprinting. Then, the substrate is placed in a plasma reaction chamber, and a nanoscale composite rough surface is further obtained on the regular nanostructure surface by plasma etching. Finally, the substrate is silane-coupling-modified and grafted with a high-fluidity flexible polymer molecular chain to obtain a surface with a transparent super-smooth anti-icing property.
[0013] Preferably, the substrate comprises any one of silicon wafer, glass, ceramic, metal and plastic.
[0014] Preferably, the temperature of the nano-imprinting is 80° C.-150° C., the pressure is 1.8 MPa-2.5 MPa, the time is 2 min-5 min, and the time of UV curing is 10 s-600 s.
[0015] Preferably, the wavelength of the ultraviolet light source for nanoimprinting is 365 nm, and the light source alignment method is optical alignment.
[0016] Preferably, the regular nanostructure is a nanoarray, and the shape of the nanoarray is a periodically arranged nanocolumnar structure with a diameter or side length of 50nm-100nm, a height of 30nm-50nm, and an interval of 20nm-80nm.
[0017] Specifically, the periodically arranged nano-columnar structures may be circular columns or rectangular columns, the diameter of the circular columns or the side length of the rectangular columns are independently 50nm-100nm, the height is 30nm-50nm, and the interval between adjacent columnar structures is 20nm-80nm.
[0018] Preferably, the coating thickness of the photoresist is 80nm-120nm.
[0019] Preferably, the photoresist comprises one of IPNR-PC1000, IPNR-PC2000, and SU-8 photoresist.
[0020] Preferably, before nanoimprinting, the substrate and the imprint template are cleaned.
[0021] The present invention uses nano-imprinting to obtain a non-planar nano-composite texture, which can ensure the transparency of the coating while meeting a certain surface roughness and reducing the solid-liquid contact area.
[0022] Preferably, the plasma etching time is 5 min-15 min.
[0023] Preferably, the gas flow rate during the plasma etching is 1 sccm-18 sccm, and the plasma power supply voltage is 400V-800V.
[0024] The nanostructure of the substrate surface after nanoimprinting before plasma etching is arranged more regularly, and the microstructure of the substrate surface becomes rough after etching, and nanoscale pits, protrusions and other structures are generated on the nanostructure formed by imprinting. This structure can effectively reduce the solid-liquid contact area and reduce the binding force between solid-liquid and solid-ice. At the same time, the composite structure can provide a larger specific surface area, providing more physical adsorption sites and reactive sites for grafted flexible polymer molecular chains. When the flexible polymer molecular chains are grafted, they can be better attached to the substrate surface, thereby increasing the grafting density.
[0025] Preferably, the silane coupling modified modifier includes at least one of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxytrimethoxysilane (KH-560), and tetraethoxysilane (TEOS).
[0026] Preferably, the modification and grafting method is: immersing the activated substrate having the nanocomposite structure in a solution containing a silane coupling modifier and a flexible polymer molecular chain; the concentration of the flexible polymer molecular chain in the solution is 0.5 mg / mL-10 mg / mL, and the concentration of the silane modifier is 0.5 mg / mL-5 mg / mL.
[0027] Preferably, the solvent of the solution containing the silane coupling modifier and the flexible polymer molecular chain is an organic solvent, and the organic solvent includes toluene.
[0028] Preferably, the flexible polymer molecular chain includes at least one of polydimethylsiloxane (PDMS), perfluoropolyether (PFPE), and long straight-chain alkane.
[0029] More preferably, the long straight-chain alkane includes at least one of n-decane, n-dodecane, n-hexadecane and n-octadecane.
[0030] Preferably, the temperature during the modification and grafting is 50° C.-80° C., and the time is 5 h-8 h.
[0031] Preferably, the grafted substrate is dried; more preferably, the drying temperature is 50° C.-80° C., and the drying time is 3 h-6 h.
[0032] The present invention uses a silane modifier to modify the activated substrate, and then grafts flexible polymer molecular chains. The flexible polymer molecular chains rely on their own chemical activity and the reaction sites provided on the surface of the material after silanization treatment to effectively chemically bond with the material surface, thereby achieving grafting.
[0033] In a second aspect, the present invention provides a transparent super-smooth anti-icing surface prepared by the method for preparing the transparent super-smooth anti-icing surface.
[0034] The surface prepared by the method for preparing the transparent super-slip anti-icing surface of the present invention has excellent light transmittance and super-slip anti-icing performance, and has broad application prospects.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The present invention uses nanoimprinting technology to obtain a non-planar nanocomposite texture, which can ensure the transparency of the coating while meeting a certain surface roughness and reducing the solid-liquid contact area. On its surface, the actual contact area between the water droplet and the solid can be only 10%-30% of that of the planar structure, which greatly inhibits the nucleation and growth of ice. In addition, the structure can reduce the growth rate of ice crystals to 1 / 5-1 / 3 of the planar structure and significantly reduce the contact time of the droplet on the surface.
[0037] (2) The present invention uses plasma to treat a substrate with a regular nanostructure, which can generate active groups such as hydroxyl groups on the substrate surface and etch the substrate to obtain a new nanocomposite structure. The generated active groups can be used as modification sites, and the nanostructure can further reduce the solid-liquid interface area.
[0038] (3) The present invention obtains a surface nanocomposite structure by combining nanoimprinting with plasma etching, and can obtain a surface with a visible light transmittance of more than 95%; after further silane modification and liquid-like flexible polymer molecular chain grafting, the freezing time can be delayed by more than 440% compared with the untreated surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the surface morphology of the substrate with regular nanostructures obtained in step (1) of Example 1;
[0040] Figure 2 The schematic diagram of the cross-sectional surface morphology of the substrate with regular nanostructures obtained in step (1) of Example 1;
[0041] Figure 3 This is a schematic diagram of the surface morphology of the substrate after activation obtained in step (2) of Example 1;
[0042] Figure 4 is the water contact angle of the transparent super-slip anti-icing surface of Example 1;
[0043] Figure 5 This is a comparison chart of the freezing time of Example 1, Comparative Example 1 and an untreated glass sheet at an ambient temperature of 15° C. at t=0s, wherein a is an untreated glass sheet, b is Comparative Example 1, and c is Example 1;
[0044] Figure 6 This is a comparison chart of the freezing time of Example 1, Comparative Example 1 and an untreated glass sheet at an ambient temperature of 15° C. when t=50s, wherein a is an untreated glass sheet, b is Comparative Example 1, and c is Example 1;
[0045] Figure 7This is a comparison chart of the freezing time of Example 1, Comparative Example 1 and an untreated glass sheet at an ambient temperature of 15° C. when t=230s, wherein a is the untreated glass sheet, b is Comparative Example 1, and c is Example 1. DETAILED DESCRIPTION
[0046] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0047] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0048] Example 1
[0049] A method for preparing a transparent super-slip anti-icing surface comprises the following steps:
[0050] (1) The glass substrate was ultrasonically cleaned with acetone and deionized water, then washed with distilled water and dried, and IPNR-PC1000 photoresist was coated on the dried substrate by spin coating; the imprint template was blown with a nitrogen gun, and then ultrasonically cleaned with acetone and deionized water and dried; the substrate and template were loaded, and the imprint temperature was set to 100°C, the loading pressure was set to 2 MPa, and the imprint time was set to 3 min, and then loading was performed. While loading, the substrate was cured with ultraviolet light for 30 s to obtain a substrate with a regular nanostructure; the surface morphology of the substrate is shown in the schematic diagram Figure 1 and Figure 2 As shown, Figure 1 It is a plane diagram. Figure 2 It is a cross-sectional schematic diagram; the size of the imprint template is 20×20 mm, and the pattern shape on the imprint template is a cylinder with a diameter of 60 nm, a height of 30 nm, and a period of 50 nm;
[0051] (2) The substrate with regular nanostructure obtained in step (1) is suspended and fixed in a plasma chamber, evacuated to a pressure of 3 Pa, introduced with 12 sccm of O2, and the plasma power supply voltage is set to 700 V. After reacting for 15 minutes, the substrate is taken out to obtain an activated substrate with a nanocomposite structure. The surface morphology of the substrate after activation is shown in FIG. Figure 3 As shown;
[0052] (3) The activated substrate with a nanocomposite structure obtained in step (2) is taken out, washed with ethanol, and dried; 1 g of PFPE with a hydroxyl end group and 0.5 g of tetraethoxysilane (TEOS) are selected, and the weighed PFPE and TEOS are slowly added to 98.5 g of toluene, and stirred at 400 rpm for 30 minutes, and the dried substrate is placed in the solution so that it is completely immersed, and the reaction container is placed in a 60°C constant temperature water bath for reaction grafting for 6 hours, and stirred at 200 rpm. After the reaction is completed, the substrate surface is rinsed with toluene 3 times, and then placed in a vacuum drying oven, and dried at 50°C and a vacuum degree of 5 Pa for 4 hours to obtain the transparent ultra-smooth anti-icing surface.
[0053] Example 2
[0054] The difference between this embodiment and embodiment 1 is that a silicon wafer is used as the substrate, and the rest is the same as embodiment 1, that is, a transparent ultra-smooth anti-icing surface is prepared on the surface of the silicon wafer in this embodiment.
[0055] Example 3
[0056] A method for preparing a transparent super-slip anti-icing surface comprises the following steps:
[0057] (1) ultrasonically cleaning a glass substrate with acetone and deionized water, then washing it with distilled water, and drying it, and coating the dried substrate with IPNR-PC1000 photoresist by spin coating; blowing the imprint template with a nitrogen gun, and then ultrasonically cleaning it with acetone and deionized water, and drying it; loading the substrate and the template, setting the imprint temperature to 140°C, the loading pressure to 2 MPa, and the imprint time to 3 min, and then loading, while loading, using ultraviolet light to cure the substrate for 30 s to obtain a substrate with a regular nanostructure; the size of the imprint template is 20×20 mm, and the pattern shape on the imprint template is a cylinder with a diameter of 60 nm, a height of 30 nm, and a spacing of 50 nm;
[0058] (2) The substrate with regular nanostructure obtained in step (1) is suspended and fixed in a plasma chamber, evacuated to a pressure of 3 Pa, introduced with 18 sccm of O2, and the plasma power supply voltage is set to 400 V. After reacting for 15 minutes, the substrate is taken out to obtain an activated substrate with a nanocomposite structure;
[0059] (3) The activated substrate with a nanocomposite structure obtained in step (2) is taken out, washed with ethanol, and dried; 1 g of PFPE with a hydroxyl end group and 0.5 g of tetraethoxysilane are selected, and the weighed PFPE and TEOS are slowly added into 98.5 g of toluene, and stirred at 400 rpm for 30 minutes, and the dried substrate is placed in the solution so that it is completely immersed, and the reaction container is placed in a 60°C constant temperature water bath for reaction grafting for 6 hours, and stirred at 200 rpm. After the reaction is completed, the surface of the substrate is rinsed with toluene 3 times, and then placed in a vacuum drying oven, and dried for 4 hours at 50°C and a vacuum degree of 5 Pa to obtain the transparent ultra-smooth anti-icing surface.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that step (1) is not performed, and the rest is the same as Example 1. That is, this comparative example does not perform nanoimprinting but adopts a planar structure.
[0062] Comparative Example 2
[0063] The difference between this comparative example and Example 1 is that step (1) is not performed, and the plasma etching time in step (2) is 30 minutes, and the rest is the same as Example 1. That is, nanoimprinting is not performed in this comparative example, and the plasma etching time is 30 minutes.
[0064] Comparative Example 3
[0065] The difference between this comparative example and Example 1 is that step (2) is not performed, and the rest is the same as Example 1. That is, this comparative example does not use plasma to activate the substrate surface and etch the microstructure.
[0066] Comparative Example 4
[0067] The difference between this comparative example and Example 1 is that step (3) is not performed, and the rest is the same as Example 1. That is, in this comparative example, the substrate obtained in step (2) is not subjected to silane modification and flexible molecular chain grafting.
[0068] The surfaces obtained in the examples and comparative examples, as well as the glass substrate and silicon wafer substrate that have not been treated in any way, were tested for static water contact angle, dynamic water sliding angle, visible light transmittance, and ice formation delay time. The test methods are as follows:
[0069] The static contact angle and dynamic sliding angle of the prepared coating were tested using a Kruss DSA100 contact angle tester. All static contact angles were measured using a 5μL water droplet, and the dynamic sliding angle was measured using a 20μL water droplet. At least five different areas were measured for each coating, and the average value was taken as the final value. The visible light transmittance of the prepared coating was tested using a TU-1950 UV-visible spectrophotometer (UV-vis). With a blank glass sheet as the background, the scanning band was 350-780nm. At an ambient temperature of 15°C, a refrigeration sheet with a refrigeration temperature of -10°C was used to test the freezing time.
[0070] The test results are shown in Table 1. Since the silicon wafer substrate is opaque, the light transmittance of the coating cannot be measured and is therefore represented by “ / ”.
[0071] Table 1 Surface test results of embodiments and comparative examples
[0072]
[0073]
[0074] The surface water contact angle of Example 1 is as follows Figure 4 As shown, Figure 5-7 : is a comparison chart of the freezing time of Example 1, Comparative Example 1 and an untreated glass sheet at an ambient temperature of 15° C., wherein a is an untreated glass sheet, b is Comparative Example 1, and c is Example 1. Figure 5 This is the comparison chart of freezing time at t = 0s. Figure 6 This is a comparison chart of the freezing time at t=50s and a comparison chart of the freezing time at t=230s.
[0075] According to the data in Table 1 and Figure 4-7 It can be seen that the surface obtained by the preparation method of the present invention has excellent transparency and anti-icing effect. The dynamic sliding angle of the untreated glass sheet is 90 °, which means that water droplets adhere to the surface and cannot slide off, and they are frozen in 50s. In Comparative Example 1, nanoimprinting was not performed on the substrate surface, resulting in a significant decrease in the anti-icing effect of the surface. In Comparative Example 2, due to the long etching time, a micron-level rough structure was produced, which made it present super-hydrophobic properties, but the transmittance decreased significantly. In Comparative Example 3, plasma etching was not performed, resulting in a deterioration in the anti-icing effect of the surface. In Comparative Example 4, the surface was not silane-modified and the flexible molecular chain was not grafted, resulting in a deterioration in the hydrophobic effect of the surface and a reduction in the anti-icing effect.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a transparent super-slip anti-icing surface, characterized in that: The following steps are involved: Coating a photoresist on the surface of the substrate, and then performing nanoimprinting to obtain a substrate with a regular nanostructure; Plasma etching is performed on the substrate having the regular nanostructure to obtain an activated substrate having a nanocomposite structure; The activated substrate surface with the nanocomposite structure is subjected to silane coupling modification and grafted with flexible polymer molecular chains to obtain the transparent super-slip anti-icing surface.
2. The method for preparing a transparent super-slip anti-icing surface according to claim 1, characterized in that: The substrate includes any one of silicon wafer, glass, ceramic, metal and plastic.
3. The method for preparing a transparent super-slip anti-icing surface according to claim 1, characterized in that: The nano-imprinting temperature is 80° C.-150° C., the pressure is 1.8 MPa-2.5 MPa, the time is 2 min-5 min, and the UV curing time is 10 s-600 s.
4. The method for preparing a transparent super-slip anti-icing surface according to claim 1, characterized in that: The regular nanostructure is a nanoarray, and the shape of the nanoarray is a periodically arranged nanocolumnar structure with a diameter or side length of 50nm-100nm, a height of 30nm-50nm, and an interval of 20nm-80nm.
5. The method for preparing a transparent super-slip anti-icing surface according to claim 1, characterized in that: The plasma etching time is 5 min-15 min.
6. The method for preparing a transparent super-slip anti-icing surface according to claim 1, characterized in that: The gas flow rate during the plasma etching is 1 sccm-18 sccm, and the plasma power supply voltage is 400V-800V.
7. The method for preparing a transparent super-slip anti-icing surface according to claim 1, characterized in that: The silane coupling modified modifier includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxytrimethoxysilane, and tetraethoxysilane; and / or the flexible polymer molecular chain includes at least one of polydimethylsiloxane, perfluoropolyether, and long straight-chain alkane.
8. The method for preparing a transparent super-slip anti-icing surface according to claim 1, characterized in that: The temperature during modification and grafting is 50°C-80°C, and the time is 5h-8h.
9. The method for preparing a transparent super-slip anti-icing surface according to claim 1, characterized in that: The modification and grafting method comprises: immersing the activated substrate with the nanocomposite structure in a solution containing a silane modifier and a flexible polymer molecular chain; the concentration of the flexible polymer molecular chain in the solution is 0.5 mg / mL-10 mg / mL, and the concentration of the silane modifier is 0.5 mg / mL-5 mg / mL.
10. A transparent super-smooth anti-icing surface obtained by the method for preparing a transparent super-smooth anti-icing surface according to any one of claims 1 to 9.